2015
DOI: 10.1016/j.jcms.2015.03.016
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of TLR3 and TLR4 in keratocystic odontogenic tumor (KCOT): A comparative immunohistochemical study in primary, recurrent, and nevoid basal cell carcinoma syndrome (NBCCS)–associated lesions

Abstract: According these findings it seems conceivable to assume that the up-regulation of TLR4 in some KCOTs can be correlated somehow to their tendency recurrence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
16
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 35 publications
3
16
0
Order By: Relevance
“…The results of this study confirm previously published data on survivin expression in KCOTs (Andric et al, 2010; De Oliveira et al, 2011;Leonardi et al, 2013). The study also demonstrated that survivin immunostaining is a feature of the basal and parabasal epithelial layers of KCOTs.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The results of this study confirm previously published data on survivin expression in KCOTs (Andric et al, 2010; De Oliveira et al, 2011;Leonardi et al, 2013). The study also demonstrated that survivin immunostaining is a feature of the basal and parabasal epithelial layers of KCOTs.…”
Section: Discussionsupporting
confidence: 92%
“…De Oliveira and co-workers showed both nuclear and cytoplasmic survivin expression (De Oliveira et al, 2011). Leonardi and colleagues suggested that apart from cytoplasmic immunostaining in primary KCOTs, lesions associated with NBCC syndrome also demonstrate nuclear staining for survivin (Leonardi et al, 2013). Our study showed nuclear expression of survivin in the basal and suprabasal epithelial layers of sporadic KCOTs and cytoplasmic survivin immunostaining in epithelial cells of PFs.…”
Section: Discussionsupporting
confidence: 57%
“…We investigated the AE1/AE3 and b-catenin immunohistochemical profile of the lesions and observed that both KCOT and OOC cyst linings showed strong and diffuse cytoplasmic, as well as membranous, cytoplasmic and nuclear immunopositivity for AE1/AE3 and b-catenin, respectively, throughout the thickness of the epithelium. Leonardi et al [39] reported that sporadic primary KCOTs showed weaker staining for b-catenin, confined to the basal and para-basal layers only, compared to sporadic recurrent and nevoid basal cell carcinoma syndrome (NBCCS)-associated KCOTs, which showed expression throughout all epithelial layers. Interestingly, nuclear expression of bcatenin was found exclusively in recurrent and NBCCSassociated KCOTs [39].…”
Section: Discussionmentioning
confidence: 99%
“…Leonardi et al [39] reported that sporadic primary KCOTs showed weaker staining for b-catenin, confined to the basal and para-basal layers only, compared to sporadic recurrent and nevoid basal cell carcinoma syndrome (NBCCS)-associated KCOTs, which showed expression throughout all epithelial layers. Interestingly, nuclear expression of bcatenin was found exclusively in recurrent and NBCCSassociated KCOTs [39]. Contradictory results were published by Hakim et al [40] showing significantly higher loss of b-catenin in syndromic than in sporadic KCOTs.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4] There are uncertainties as to whether differences exist in the biologic behavior of Gorlin syndromeeassociated KOTs (SKOTs) and nonsyndromic KOTs (NSKOTs). In this respect, studies evaluating the proteins involved in cell cycle and apoptosis, [5][6][7] as well as extracellular matrix components 8 and proteases, [7][8][9][10][11] support the existence of a different biologic behavior in SKOTs and NSKOTs.…”
mentioning
confidence: 96%